Activity of ceftolozane–tazobactam and comparators against Pseudomonas aeruginosa from patients in different risk strata – SMART United States 2016–2017. (March 2020) - Lob, Sibylle H.; Hoban, Daryl J.; Young, Katherine; Motyl, Mary R.; Sahm, Daniel F.
Highlights: Infections caused by Pseudomonas aeruginosa (PA) are often difficult to treat. In the US, prevalence of PA and susceptibility to β-lactams differed by risk strata. Prevalence of PA was higher and susceptibility lower in ICU than in non-ICU wards. Susceptibility was lower in isolates from younger patients, and from respiratory infections. Ceftolozane–tazobactam maintained activity against >90% of PA in all risk strata. Abstract: Objectives: Infections caused by Pseudomonas aeruginosa are often difficult to treat. Knowledge of the risk of infection with resistant P. aeruginosa would allow more discriminatory prescribing of broad-spectrum antimicrobials. Using clinical isolates collected as part of the Study for Monitoring Antimicrobial Resistance Trends (SMART), we examined the activity of commonly used β-lactams, levofloxacin, and ceftolozane–tazobactam (C/T), an antipseudomonal cephalosporin/β-lactamase inhibitor approved in the United States and over 60 countries worldwide, against P. aeruginosa isolates from patients in different risk strata. Methods: In 2016–2017, 25 hospitals in the US each collected up to 250 consecutive gram-negative bacilli per year from respiratory tract (RTI), intraabdominal (IAI), and urinary tract (UTI) infections. MICs of 9, 964 isolates (including 1, 887 P. aeruginosa ) were determined using CLSI broth microdilution and interpreted with CLSI breakpoints. Results: Susceptibility of all P. aeruginosa isolates combined was 94.7% to C/T and 76.8%, 77.0%, 70.2%, and 69.0% to ceftazidime, meropenem, piperacillin–tazobactam, and levofloxacin, respectively. Susceptibility to the β-lactam comparators was 8–11 percentage points lower among ICU than non-ICU isolates, 7–11 points lower in isolates collected ≥48 h than <48 h post-admission, 1–5 points lower in patients <65 years of age than older patients, and 3–12 points lower in RTI than IAI and UTI isolates. C/T maintained activity against >90% of P. aeruginosa isolates in all risk strata and against 75–88% of isolates nonsusceptible to ceftazidime, meropenem, or piperacillin–tazobactam. Conclusions: C/T represents a promising new treatment option even in strata in which the risk of infection with β-lactam-nonsusceptible P. aeruginosa appeared higher.